The Influence of Using Capcut Media on Science Learning Outcomes of Class VII Students of SMP Negeri 1 Maiwa in Enrekang - Nisma Nisma; Usman M; Hasanuddin B; Sam Hermansyah; Hasan Hasan (Universitas Muhammadiyah Enrekang, 2023)
This study used a quantitative method and an experimental type of research with the aim of intuitively testing the effect of using Capcuit media on science learning outcomes for class VII students at SMP Negeri 1 Maiwa, Enrekang Regency. The research population consisted of all grade VII students of SMP Negeri 1 Maiwa Kabuipaten Enrekang and the samples taken were 28 students of class VII SMP Negeri 1 Maiwa Kabuipaten Enrekang and Cluister Randoim Sampling. There are 2 variables in this study, the first is the independent variable, namely the effect of using Capcuit media (x) and the second dependent variable is the results of learning science in class VII 3 students (y). This research was conducted at SMP Negeri 1 Maiwa Kabuipaten Enrekang.Data collection techniques used observations, tests, documentation, the test results data that had been collected were then analyzed using the Ruimuis mean. Based on the results of data analysis, it was obtained a value of X = 84.07 > a value of Y = 76.14 so that it can be seen that there is an effect of using Capcuit media on science learning outcomes for class VII students of SMP Negeri 1 Maiwa Kabuipaten Enrekang. The results of this study concluded that there was an effect of using Capcuit media on science learning outcomes for class VII students of SMP Negeri 1 Maiwa Kabuipaten Enrekang. This indicates that the working hypothesis which states that there is an effect of using Capcuit media on science learning outcomes for class VII students of SMP Negeri 1 Maiwa Kabuipaten Enrekang, is accepted.